2021
DOI: 10.51680/ev.34.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Review of national financial education policies aimed at the young

Abstract: Purpose: The paper investigates and synthesizes an in-depth overview of national financial education policies and strategies aimed at the young, highlights the best practices, gives recommendations for the most efficient financial education efforts at the national level and the implementation of an efficient financial education policy in Croatia. Methodology: The analysis is conducted as a case study of financial education policies and strategies aimed at the young of the countries that achieved the best resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Indeed, overall, financial education is a crucial factor in helping consumers make better financial decisions. Financial education is a process of improving consumers' understanding of financial terms and concepts and acquiring skills and confidence crucial to making efficient and informed financial decisions and, ultimately, achieving personal welfare (Lučić, Uzelac, and Gaćina, 2021). Research has shown that people with more financial literacy make better financial decisions and show positive financial behaviors (Nicolini and Haupt, 2019).…”
Section: Consumer and Business Risksmentioning
confidence: 99%
“…Indeed, overall, financial education is a crucial factor in helping consumers make better financial decisions. Financial education is a process of improving consumers' understanding of financial terms and concepts and acquiring skills and confidence crucial to making efficient and informed financial decisions and, ultimately, achieving personal welfare (Lučić, Uzelac, and Gaćina, 2021). Research has shown that people with more financial literacy make better financial decisions and show positive financial behaviors (Nicolini and Haupt, 2019).…”
Section: Consumer and Business Risksmentioning
confidence: 99%